Sero-epidemiological survey for brucellosis, leptospirosis, and toxoplasmosis in free-ranging Alouatta caraya and Callithrix penicillata from Sao Paulo State, Brazil - Molina, Camila Vieira; Catao-Dias, Jose Luiz; Ferreira Neto, Jose Soares; Vasconcellos, Silvio Arruda; Gennari, Solange Maria; Valle, Rodrigo Del Rio do [UNESP]; Souza, Gisele Oliveira de; Morais, Zenaide Maria de; Vitaliano, Sergio Netto; Strefezzi, Ricardo De Francisco; Bueno, Marina Galvao (Wiley-Blackwell, 2014)
Background and MethodsSera were tested for Brucella spp., Leptospira spp. and Toxoplasma gondii antibodies in 68 free-ranging New World monkeys from a forest fragment of the BrazilianCerrado.Results and ConclusionAll animals were negative for Brucella spp. and Leptospira spp. However, 75% of Alouatta caraya and 16.6% of Callithrix penicillata were positive for T. gondii. The implications for conservation and health management are discussed.
Keywords: Alouatta; Brucella spp; Callithrix; environmental health; Leptospira spp; New World monkeys; serology; Toxoplasma gondii